KEMAMPUAN GURU DALAM MENYAMPAIKAN MATERI SURAH AL-KAFIRUN PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS VI MI MAMBAUL ULUM PUNGGUR KECIL - IMAM SANUSI (Cendekia, 2020)
The author is interested in researching this in order to find out: 1) the ability of teachers to deliver learning materials that are facts, 2) conceptual, 3) principles, 4) and procedural in the subject of Al-Qur'an Hadith Class VI at MI Mambaul Ulum Punggur Kecil Academic Year 2019/2020 with the subject matter "How is the teacher's ability to convey learning materials that are facts, concepts, principles and procedures in the subject of Al-Quran Hadith class VI MI Mambaul Ulum Punggur Kecil?. The method used is descriptive method with a quantitative approach. The research location is at MI Mambaul Ulum Punggur Kecil, Sungai Kakap District, Kubu Raya. Data obtained from the implementation of teaching and learning activities, data collection tools: observation, interviews, and documentation studies. Furthermore, it was analyzed by using a percent assessment and described descriptively in narrative form. The results of this study indicate that: 1) The teacher's ability to deliver factual learning material with a score of 80% is classified as good. 2) conceptual in nature, the score of 87.5% is good. 3) In principle, the score of 87.5% is good. 4) It is procedural with a score of 84% which is good. Based on the results of research conducted by researchers regarding the ability of teachers, it can be concluded that the ability of teachers to deliver cognitive material is classified as good. However, to support the achievement of the maximum learning process, teachers and schools should use / provide adequate learning media to make it easier to achieve learning objectives.